Profile of Phenolic and Antioxidants Activity from Seaweed Extract Turbinaria conoides and Eucheuma cottonii - Rini Yanuarti; N. Nurjanah; Effionora Anwar; Taufik Hidayat (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Seaweed extract has ability to reduce some effects of free radicals because of phenolic compound. The purpose of this study was to determine total phenolic content, total flavonoids and antioxidant activity of seaweed extract from Turbinaria conoides and Eucheuma cottonii with different solvents. The extraction was carried out by n-hexane (non-polar) solvent, ethyl acetate (semi-polar) and methanol (polar). The results showed that the highest total phenol and flavonoids were found in  extract of Turbinaria conoides with ethyl acetate 211.00 mg GAE/g and 157.16 mg QE/g. Seaweed Eucheuma cottonii extract using methanol solvent had a higher phenol content 141.00 mg GAE/g, whereas the highest flavonoid content found in ethyl acetate solvent (35.1771 mg QE/g). The very strong antioxidant activity (< 50 μg/mL) was found in Turbinaria conoides and Eucheuma cottonii which extracted by methanol solvent (15.148 μg/mL and 23.154 μg/mL). Seaweed Turbinaria conoides and Eucheuma cottonii had a great potential as natural antioxidant.